Compositional methodology for conducting the research of municipalities’ economic development - Elena B. Dvoryadkina; Anna M. Ermakova; Natalia A. Istomina (Journal of New Economy)
At present, the scientific paradigm of municipal economics is being formed, different theories and concepts related to municipal research are being studied and discussed. Therefore, there is a need for a relevant methodology to investigate the economic development of municipalities. Science has established certain approaches to explore the issues of municipal economy, yet the extension of the subject of re gional and municipal economics stimulates the proposal of the new ones. The paper aims to validate a new compositional methodology for conducting the research of municipalities’ economic development. The methodological basis of the study con sists of the theories of regional development, the paradigm of municipal economics, as well as the spatial, evolutionary and systems approaches. The paper relies on a host of general scientific methods including reviewing, comparative analysis, and system atisation. Based on revealing the essence of the term “composition” and presenting the arguments confirming the appropriateness of using it in the regional economics discourse the authors formulate the principles of the compositional methodological approach to the research of municipalities’ economic development, which include the principles of equipoise, dynamism, unity and subordination, integrity, harmony. The compositional methodological approach benefits from the three underlying meth odologies: spatio-temporal, evolutionary, and systems ones, the application of which in the aggregate allows conceptualising the basic propositions for the research of the municipalities’ economic development through the principles of composition. The developed original approach will help create a methodological foundation for inves tigating the municipalities’ economic development in conditions of a new axiological paradigm emerging in society.